Reconciliation Through Narrative: Toward a Theology of Spiritual Care in Public Health Care - Lasair, Simon (Practical theology, 2017)
In the West, chaplains are often employed by state mandated and state funded health care institutions. Because such western institutions are predicated upon the principles of secular liberalism, understanding the work of chaplains within such contexts is an urgent intellectual need. This paper seeks to describe such work through a Christian theological lens, arguing chaplaincy work can counter balance frequent experiences of alienation when people encounter health care systems as patients. Drawing upon the work of Slavoj iek, Rowan Williams, and Mieke Bal, this paper describes spiritual care as being a specific kind of narrative practice that can prompt the work of reconciliation in chaplaincy clients themselves, in the clients' lived experience, and in their experience of health care systems.